أساليب التنشئة الأسرية وعلاقتها بالعنف في الوسط المدرسي - مأمون، محمد علي, تركي، عبد المالك (جامعة الوادي university of Eloued, 2020)
ملخص الدراسة بالعربية: تهدف الدراسة الحالية الى التعرف على علاقة أساليب التنشئة الأسرية بالعنف في الوسط المدرسي لدى تلاميذ سنة الثالثة والرابعة متوسط ومحاولة الوصول الى حلول للحد من ظاهرة العنف المدرسي، وذلك انطلاقا من تساؤل رئيسي مفاده هل توجد علاقة بين أساليب التنشئة الأسرية والعنف في الوسط المدرسي؟ لتتفرع عنه تساؤلات فرعية أهمها: هل توجد علاقة بين أسلوب الإهمال الأسري والعنف في الوسط المدرسي؟ هل توجد علاقة بين الأسلوب الديمقراطي والعنف في الوسط المدرسي؟ هل توجد علاقة بين أسلوب التسلط الأسري والعنف في الوسط المدرسي؟ اعتمدت الدراسة على المنهج الوصفي التحليلي باعتباره يتماشى مع طبيعة البحث والكشف عن علاقة أساليب التنشئة الأسرية بالعنف المدرسي، وكان من المفترض ان تجرى دراستنا على عينة مكونة من 95تلميذا والذين يدرسون بقسمي الثالثة والرابعة متوسط بمتوسطات بلدية ورماس.Abstract: Firstly, the current study aimes to recognize the relationship of the methods of family upbringing with violence in the school environment among students .Further more, to reach reducing the phenomenon of violence family. Beganing of is there a relationship between the styles of family upbringing and violence in the school environment ? and many question such : * Is there a relationship between family neglect and violence in the school environment? * Is there a relationship between the democratic style and violence in the school environment? *Is there a relationship between family bullying and violence in the school environment? Finally, the study built on the descriptive and analytical approach as it is in line with the nature of the research and reveals the relationship of family upbringing methods to school violence. Supposed to study it should be on the sample of 95 pupils that they study in 3 & 4 level in Ourmes's middle school.
دراسة ميدانية بمتوسطتي حريز التجاني وسالم العربي بورماس ولاية الوادي
Keywords: التنشئة الإجتماعية، العنف المدرسي; Socialisation, violence scolaire; Socialization, school violence